Mobile clinics help UMP staff keen on health - Siti Nurfarmy, Ibrahim (2020)
Pekan, 13 July 2020 - Keen on the health of employees, University Health Centre (PKU) organized a Mobile Clinic Program that encourages university staff to check their health status.